The Westminster Dog Show: A Probe into the Human/Dog Relationship - Urban, Ashley (Université d'Ottawa | University of Ottawa, 2021)
This research paper explores the human-dog relationship in the context of the Westminster Kennel Club Dog Show. Many researchers have explored human-dog relationships across a variety of settings (Haraway, 2003, Simon, 2015, Anderson, 1986 & Porter, 2018). I have conducted an ethnographic probe to review videos and other documentation of the Westminster Kennel Club Dog Show to explore the relationships between humans and dogs. I relied on interviews and videos surrounding the dog show to document how humans perceived their relationships with their dogs and how they interacted with their dogs. Common themes emerged from the interviews and interactions that were used to help describe the qualities of this human-dog relationship within the context of the Westminster Kennel Club Dog Show. I suggest that the relationships examined as part of this probe showcased qualities of autonomic beings coming together for a common purpose. The relationships reviewed showcased a non-contingent connectedness between humans and dogs where they shared connectivity in their actions and emotions. Through the individual relationships examined, I suggest that these relationships exemplify companionship relationships. I also explore the cohistories of humans and dogs through the example of the relationship between humans and the Bulldog breed to showcase how social factors, like class and sport have shaped human-dog relationships. I explore the concept of dog breeding and suggest that although breeding involves manipulation of a dog’s genetics, the overall concept of breeding is an example of biopower that helps encourage breeders to breed with good intentions to produce high-quality and healthy dogs. Lastly, I explore human-dog relationships on a local and global level to suggest that this multi-species relationship can be described as an anthropo-zoo-genesis that is acted out through the production of affect towards one another.